Characteristic Nest Angelwing Clam (Pholas orientalis Gmelin, 1791) in the Area of Kelang Beach - Khairul Khairul; Rusdi Machrizal; Rivo Hasper Dimenta (Jambura Journal of Animal Science, 2020)
A clam angelwing is one kind of razor clam. His life Habitat is found in the Kelang Beach district of Serdang Bedagai, North Sumatera Province. The purpose of this research is to know the characteristics of tembarang shell nests. This research is an exploratory, discrete study. The findings Data are narrated and discussed based on the relevant literature review. Based on the findings in the field, the characteristics of the nest angelwing clam are listed as follows: Distance from the shoreline between 30-70 meters, The diameter of the nest length is 0.5-1.5 cm and the width is 0.3-1 cm, the holes are round and round oval, usually holes consist of 1-5 pieces. Hole depth 10-40 cm, on the surface of the hole there are shavings or piles of sand, and 1 hole filled 1 individual. Average water quality observation during research: water temperature (29-30 °C), Water brightness (25-40 cm), water pH (7,5-7,9), dissolved oxygen (5,6-5,9 ppm), and salinity (29-30 ppt).